Identification of the lytic origin of DNA replication in human cytomegalovirus by a novel approach utilizing ganciclovir-induced chain termination. - Hamzeh, F M (1990)
Infection with human cytomegalovirus in the presence of the antiviral nucleotide analog ganciclovir results in continuing low-level viral DNA synthesis and the accumulation of relatively small fragments of double-stranded progency DNA. These fragments consistently proved to represent amplification of sequences from only one small section of the viral genome (EcoRI-V) lying near the center of the unique L segment. Further mapping revealed that the viral sequences represented in these fragments occurred in gradients of abundance that decreased in both directions from a point near 0.35 to 0.4 map unit. The proportion of amplified sequences increased with both time after infection and dosage of ganciclovir used. We conclude that the primary lytic cycle replication origin of human cytomegalovirus lies within a 3- to 4-kb region immediately upstream and to the right of the promoter for the single-stranded DNA-binding protein (DB140). The amplified origin-containing DNA molecules appeared to arise by continuing rounds of bidirectional initiation on truncated fragments of the genome that were generated as a result of chain termination effects induced by the incorporation of ganciclovir into the viral DNA. Inspection of the DNA sequence in the vicinity of ori-Lyt revealed a large complex upstream region that may be a noncoding intergenic domain and that bears no homology to any previously described herpesvirus origin. This 2.5-kb region includes many duplicated and inverted sequences, together with consensus CRE/ATF and other transcription factor-binding sites, and an interesting set of 23 copies of an interspersed decamer consensus element AAAACACCGT that is also conserved at the equivalent locus in simian cytomegalovirus. This work represents the first identification of an origin domain in a cytomegalovirus genome and is the first demonstration of a bidirectional mechanism for any herpesvirus lytic cycle origin.